Xenotransplantation of cryopreserved human ovarian tissue - a systematic review of MII oocyte maturation and discussion of it as a realistic option for restoring fertility after cancer treatment - Dittrich, Ralf; Lotz, Laura; Fehm, Tanja; Kruessel, Jan; Von Wolff, Michael; Toth, Bettina; Van Der Ven, Hans; Schuering, Andreas N.; Wuerfel, Wolfgang; Hoffmann, Inge; Beckmann, Matthias (Fertility and Sterility, 2015)
To systematically review the reporting of MII (MII) oocyte development after xenotransplantation of human ovarian tissue.Systematic review in accordance with the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA).Not applicable.Not applicable.Formation of MII oocytes after xenotransplantation of human ovarian tissue.Any outcome reported in Pubmed.Six publications were identified that report on formation of MII oocytes after xenotransplantation of human ovarian tissue.Xenografting of human ovarian tissue has proved to be a useful model for examining ovarian function and follicle development in vivo. With human follicles that have matured through xenografting, the possibility of cancer transmission and relapse can also be eliminated, because cancer cells are not able to penetrate the zona pellucida. The reported studies have demonstrated that xenografted ovarian tissue from a range of species, including humans, can produce antral follicles that contain mature (MII) oocytes, and it has been shown that mice oocytes have the potential to give rise to live young. Although some ethical questions remain unresolved, xenotransplantation may be a promising method for restoring fertility. This review furthermore describes the value of xenotransplantation as a tool in reproductive biology and discusses the ethical and potential safety issues regarding ovarian tissue xenotransplantation as a means of recovering fertility.
EVALuna2:17543